تأثير مستويات مختلفة من سماد البيوغاز الجاف وكمبوست التبغ في نمو وإنتاجية البطاطا العادية المزروعة في محافظة طرطوس - زيدان, علي; الزعبي, محمد; ديب, ميس (Latakia University Journal -Biological Sciences Series, 2018)
نفذ البحث في مركز البحوث العلمية الزراعية، في طرطوس، في العروة الربيعية، من الموسم الزراعي لعام2017، وذلك بدراسة تأثير خلط وإضافة ثلاثة مستويات من سماد البيوغاز الجاف B))(12, 8, 4م3/ دنم) مع مستويين من كمبوست التبغ (T)(4, 2 م3/ دنم)، بالإضافة إلى معاملة شاهد بدون تسميد، ومعاملة المزارع (تسميد عضوي ومعدني) في نمو وإنتاجية محصول البطاطا العادية (صنفSpunta). واعتمد تصميم العشوائية الكاملة في تصميم البحث وبواقع ثلاثة مكررات لكل معاملة، و27 نباتاً في المكرر الواحد. أظهرت نتائج الدراسة تأثيراً إيجابياً لإضافة مزيج سماد البيوغاز وكمبوست التبغ في تحسين نمو وإنتاجية محصول البطاطا. إذ لوحظ زيادة في جميع مؤشرات النمو المدروسة مع زيادة معدلات إضافة كلا السمادين،حيث أعطت معاملة المزارع ومعاملة إضافة السماد المختلط 4 م3كمبوست التبغ+ 12م3 سماد البيوغاز الجاف للدنم أعلى قيمة لكل من المؤشرات متوسط ارتفاع النبات59.5) ، 46.08 سم) على التوالي ، والوزن الرطب والجاف للنبات (95 ، 12.55غ)على التوالي. بينما أعطت معاملة إضافة السماد المختلط 4م3كمبوست التبغ+ 4م3 سماد البيوغاز الجاف للدنم أعلى قيمة لمساحة المسطح الورقي (3066 سم2)، ودليل المسطح الورقي (1.84)، وأعلى قيمة لإنتاج النبات (621.9 غ/نبات)، وإنتاج وحدة المساحة (3.544 كغ/م2). The research was carried out at the Center for Agricultural Scientific Research, in Tartous, in spring season 2017, by studying the effect of mixing and adding three levels of dry biogas fertilizer (B) (4,8,12 m3/dunm ) with two levels of tobacco compost(T) (2,4 m3/dunm), As well as the treatment of non-fertilized as control treatment, and the treatment of farmers (organic and mineral fertilization) in growth and productivity of the regular potato crop(cult. Spunta).The Completely Randomized Design was adopted in the design of the research, with three replicates for each treatment, and 27 plants per replicate. The results of the study showed a positive effect for the addition of biogas and tobacco compost mixture to improve the growth and productivity of potato crop. The increase in all growth indicators was observed with increasing rates of addition of both fertilizers. The treatment of farmer and of the addition of mixed fertilizer 4 m3 tobacco compost + 12 m3 dry biogas fertilizer for the dunm gave the highest value for each of the indicators plant height (59.5 , 46.08 cm) ) respectively, and the fresh and dry weight of the plant (95 ,12.55 g) respectively. While the treatment of the addition of mixed fertilizer 4 m3 tobacco compost + 4 m3 dry biogas fertilizer for the dunm gave the highest value for The leaf surface area (3066 cm2), leaf surface index (1.84m2/m2),and the highest plant productivity (621.9g/plant) and unit area productivity (3.544 kg/m2).